Three-level modified sine wave inverter equipped with online temperature monitoring system - Suroso Suroso; Ahmad Khafidz; Winasis Winasis; Hari Siswantoro (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Research and development on power converters are getting more interesting in recent years. It is also buttressed by rapid development in related fields, such as power semiconductor, digital advanced control, magnetic material and use of power converters in many sectors.  In addition to the power quality matter, simplicity of inverter circuits is another notable aspect that should be considered toward economical feature. Adding the quantity of power switches will increase complexity of overall inverter circuits. This paper discusses a circuit configuration of three-level modified sine wave neutral point shorted power inverter which work converting dc power into ac power with less number of power switches. To improve the performance and feature of inverter circuits, the inverter was equipped with online temperature monitoring, and overheat protection based on internet of things. Adding online temperature monitoring system makes easier in monitoring of circuits to prevent the excessive faults of inverter. Some computer based test data are shown and discussed. Furthermore, experiment results of the inverter prototype, and its online monitoring system are presented. Test outputs demonstrated that the proposed system worked properly generating a three-level modified sine wave voltage, with online temperature monitoring system.